2010
DOI: 10.1177/147323001003800631
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Depression Mood Disorder on the Adverse Drug Reaction Incidence Rate of Anticancer Drugs in Cancer Patients

Abstract: The aim of this study was to explore the impact of depression mood disorder on the incidence of adverse drug reactions of anticancer drugs in cancer patients. The Hamilton Depression Scale 17 was used to evaluate the depression mood disorder level in 73 cancer patients before chemotherapy. Pharmacists monitored adverse drug reactions during the chemotherapy period. The relationship between depression mood disorder level and the incidence of adverse drug reactions was analysed. The frequency and extent of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…Clinical evidences indicated that anorexia nervosa often occurs in individuals with stress, anxiety-like, or depressionlike behavior (Lian et al, 2017;Lloyd et al, 2019), suggesting the possible association between mood disorder and anorexia. Similar to this finding, our previous work also noted that cancer chemotherapy patients with severe depression seemed more likely to have frequent and severe adverse drug reactions including anorexia, nausea, and fatigue (Zhou et al, 2010). Nausea and vomiting, one of the most terrible adverse reactions experienced by cancer patients, is associated with multiple risk factors including gender, age, anticancer drug dose, history of morning sickness, and alcohol intake.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Clinical evidences indicated that anorexia nervosa often occurs in individuals with stress, anxiety-like, or depressionlike behavior (Lian et al, 2017;Lloyd et al, 2019), suggesting the possible association between mood disorder and anorexia. Similar to this finding, our previous work also noted that cancer chemotherapy patients with severe depression seemed more likely to have frequent and severe adverse drug reactions including anorexia, nausea, and fatigue (Zhou et al, 2010). Nausea and vomiting, one of the most terrible adverse reactions experienced by cancer patients, is associated with multiple risk factors including gender, age, anticancer drug dose, history of morning sickness, and alcohol intake.…”
Section: Discussionsupporting
confidence: 80%
“…In our previous work, we found that the frequency and extent of subjectively experienced adverse drug reactions (anorexia, nausea, and fatigue) in cancer chemotherapy patients seemed to be well in line with the severity of their depression (Zhou et al, 2010). Chronic stress pretreatment might aggravate the vomiting process; however, the underlying mechanism is still not clear.…”
Section: Introductionmentioning
confidence: 95%
“…Depression has been found in multiple populations to be associated with increased ADEs. [1618] It is currently unclear why depression was higher in ED visits for ADE in non-dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio realizado por Zhou et al (47) se encontró que la frecuencia y la extensión de las reacciones adversas a los medicamentos no están relacionadas con la depresión, pero sí lo está la experiencia subjetiva que el paciente tiene ante estas reacciones (anorexia, nausea y fatiga).…”
Section: Factores Psicológicos Que Disminuyen La Probabilidad De Adherenciaunclassified